Measurements of the 234U(n,f) cross section using quasimonoenergetic beams in the keV and MeV range and a Micromegas detector assembly - Stamatopoulos, A.; Kanellakopoulos, A.; Kalamara, A.; Tsinganis, A.; Diakaki, M.; Kokkoris, M.; Michalopoulou, V.; Axiotis, M.; Lagoyannis, A.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
N/A